2007
DOI: 10.1016/j.jacc.2007.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Antibodies to an Oxidized Low-Density Lipoprotein Epitope Induce Rapid Regression of Atherosclerosis in Apobec-1−/−/Low-Density Lipoprotein Receptor−/−Mice

Abstract: Human IgG1 against a specific oxLDL epitope can induce rapid and substantial regression of atherosclerotic lesions, possibly by stimulating lipid efflux and inhibiting macrophage recruitment. These recombinant human antibodies could represent a novel strategy for rapid regression/stabilization of atherosclerotic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 15 publications
5
99
0
2
Order By: Relevance
“…26 A human recombinant IgG specific for the MDA-modified apo B peptide p45 inhibits the development of atherosclerosis in hypercholesterolemic mice and induces regression of lesions when combined with cholesterol lowering. 27,28 Studies performed on cultured cells have shown that immune complexes of this antibody and oxidized LDL inhibit cytokine release from monocytes through interaction with the inhibitory FcγIIb receptor. 29 Treatment of obese, hypercholesterolemic non-human primates with this antibody resulted in lower plasma levels of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…26 A human recombinant IgG specific for the MDA-modified apo B peptide p45 inhibits the development of atherosclerosis in hypercholesterolemic mice and induces regression of lesions when combined with cholesterol lowering. 27,28 Studies performed on cultured cells have shown that immune complexes of this antibody and oxidized LDL inhibit cytokine release from monocytes through interaction with the inhibitory FcγIIb receptor. 29 Treatment of obese, hypercholesterolemic non-human primates with this antibody resulted in lower plasma levels of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized LDL cholesterol (oxLDL) is generally accepted as an Ag that activates the adaptive immune system after recognition by APCs such as macrophages and dendritic cells (DCs) (8). Although, Ab treatment against a specific epitope of oxLDL, ApoB100, has been shown to induce regression of atherosclerosis, the effect of modulating immune responses on regression has not been explored (9). T cells are important in the process of atherosclerosis and affect all stages of the disease process.…”
mentioning
confidence: 99%
“…However, we have recently presented an independent association between high levels of IgG antibodies to apoB-100 peptides and a low degree of carotid stenosis ), lower risk of myocardial infarction (Sjogren et al 2008), and a lower risk for progression of coronary disease in diabetic patients ). The atheoprotective effect of IgG has also been shown in experimental studies using human IgG1 specific for a malondialdehyde-modified apoB-100 peptide (Schiopu et al 2004;Schiopu et al 2007). In accordance, we found in the present study increased levels of Th2-induced apoB/IgG1 immune complexes in the circulation of cBSA immunized mice, indicating a capture of oxidized LDL antigens at the injection site and a subsequent presentation by APCs, resulting in atheroprotection.…”
Section: Discussionmentioning
confidence: 82%